2023
DOI: 10.1371/journal.pntd.0011302
|View full text |Cite
|
Sign up to set email alerts
|

Self-care practices and health-seeking behaviours in patients with dengue fever: A qualitative study from patients’ and physicians’ perspectives

Abstract: Introduction Outpatient management for dengue fever is the mainstay of treatment for most dengue cases. However, severe dengue can develop rapidly while patients are at home. Understanding the self-care practices and healthcare-seeking behaviours among dengue patients managed as outpatients will help improve the delivery of care to these patients. Objective This study aimed to explore the self-care practices, health-seeking behaviour and outpatient management of dengue fever from the perspectives of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…For primary care providers, improving cost-effectiveness not only enhances their attractiveness, but also significantly influences patients' choice preferences and their transfer behavior. Some studies have shown that cost is a key factor in patient decision-making when faced with diverse healthcare options 28 30 . At the same time, relevant studies have emphasized how price transparency and cost reductions are effective in increasing patient demand for primary healthcare services, especially during non-emergency routine care 31 , 32 .…”
Section: Theoretical and Hypotheses Developmentmentioning
confidence: 99%
“…For primary care providers, improving cost-effectiveness not only enhances their attractiveness, but also significantly influences patients' choice preferences and their transfer behavior. Some studies have shown that cost is a key factor in patient decision-making when faced with diverse healthcare options 28 30 . At the same time, relevant studies have emphasized how price transparency and cost reductions are effective in increasing patient demand for primary healthcare services, especially during non-emergency routine care 31 , 32 .…”
Section: Theoretical and Hypotheses Developmentmentioning
confidence: 99%
“…Some participants who have abnormal blood sugar and uric acid values are given education to do followup checks at the nearest healthcare facility. The community needs to have a good understanding of mosquito eradication efforts, larvae, and environmental health hygiene efforts, so that people do not contract dengue fever and recognize the signs and symptoms of dengue hemorrhagic fever so that they know when is the right time to seek help from health workers (Boonchutima et al, 2017) (Ng et al, 2023).…”
Section: Health Hygienementioning
confidence: 99%